Pengaruh Harga dan Kualitas Produk terhadap Kepuasan Konsumen Pengguna Smartphone Sony pada PT Maju Jaya Cicaheum Bandung - Tinneke Hermina (Jurnal Wacana Ekonomi, 2017)
The purpose of this study was to determine the effect of Price (X1) and Product Quality (X2) on consumer satisfaction (Y) of Sony Smartphone users at PT. Maju Jaya Cicaheum Bandung. This is due to the assumption that the price and product quality of Sony smartphones are not what consumers expect, so that consumers feel dissatisfied with Sony Smartphone products. This can be seen from the data obtained by researchers which strengthens the indication of problems related to these three variables. The hypothesis used in this study is that there is an effect of price and product quality on consumer satisfaction of Sony Smartphone users at PT. Maju Jaya Cicaheum Bandung. This study used a quantitative descriptive method which was carried out on 100 respondents measured by a Likert scale who were all Sony Smartphone users at PT. Maju Jaya Cicaheum Bandung. The data processing techniques used were validity and reliability tests, classic assumption tests (normality, heteroscedasticity), hypothesis testing, multiple linear regression, and the coefficient of determination. The tools used are Microsoft Excel software and SPSS version 20.0. The results of this study indicate that the variable price (X1) and product quality (X2) have a simultaneous effect on consumer satisfaction of Sony Smartphone users at PT. Maju Jaya Cicaheum Bandung. Price variable (X1) has no partial effect on customer satisfaction. but product quality (X2) partially affects customer satisfaction.